Decriminalize Sexual Relationships in Minors - Tafur Gupioc, Esperanza (2015)
Crimes against sexual free demand sexual indemnity are those who have suffered the greatest number of changes in the criminal justice system, particularly laws that variedfrom28251whole concept of sexual violation and 28704 to change various articles of the criminal code, increasing the forcible detention of people between 14to 18 years regardless of sex is consensual or full capacity, ignoring the sexual maturation and psychological that occurs at this stage of the biological development of people. The decriminalization of consensual sex among minors, although it would be necessary, it is premature because the previously state must develop an appropriate policy aimed at preventing.